Validity and Reliability of Polar V800 Smart Watch to Measure Cricket-Specific Movements - Subhashis Biswas; Supratim Guha; Rupayan Bhattacharya (OVS LLC, 2022)
The study purpose was to assess the reliability and validity of Polar V800 smart watch in measuring various cricket-specific movements. Materials and methods. Only one trained male volunteer was selected to perform all the cricket specific movements to minimize individual error and eliminate between-subject variability. Polar V800 obtained distances were compared with real field markings. Results. Split-half Reliability Statistical method has been used and 'r' score for the measurements taken has been found to be 0.93. 95% confidence intervals also express a good reliability score. The criterion validity method was used to determine the validity of the dataset. The Pearson correlations (r) have been found ranging from 0.86 to 0.99. Predicted best fit line of linear regression has been found as y = 0.9722 X + 0.0046 (where y = observed value, X = real field distance). One way ANOVA followed by Tukey's post hoc test on observed 10m sprint, 20m sprint and run-a-three movements show maximum significant difference with other cricket-specific movements. The mean percentage of bias for all cricket-specific movements has been found to be -2.20 ± 13.17. Conclusions. The study reveals that Polar V800 smart watch has an acceptable accuracy, reliability, and validity for measuring various cricket specific movements with certain limitations.